The Things that Make for Peace: Jesus and Eschatological Violence - Nickel, Jesse P. (Zeitschrift für die neutestamentliche Wissenschaft und die Kunde der älteren Kirche, 2021)
Frontmatter -- Contents -- Preface & Acknowledgements -- Chapter 1 Violence, Eschatology, and the Life and Ministry of Jesus -- Chapter 2 Violence in Second Temple Jewish Eschatological Writings -- Chapter 3 Eschatologically-Motivated Violence in Second Temple Jewish History -- Chapter 4 Jesus and Revolutionary Violence -- Chapter 5 Jesus’s Rejection of Eschatological Violence In the Synoptic Gospels -- Chapter 6 Jesus and Eschatological Conflict -- Chapter 7 Conclusion -- Bibliography -- Index of Ancient Sources -- Subject Index